Revisiting surprise appeals: How surprise labeling curtails consumption - Schumacher, Anika; Goukens, Caroline; Geyskens, Kelly; Nielsen, Jesper H. (Journal of Consumer Psychology, 2025)
AbstractElements of surprise are effective tools for attracting consumers' attention and influencing their choices. Consequently, a common marketing practice is to promote a product or consumption experience as surprising. An example is Netflix, which relabeled its “Play Something” feature as “Surprise Me.” While surprise labeling positively influences choice, across 10 studies and a variety of consumption experiences, this research shows that adding a surprise label can negatively influence actual consumption. Particularly when a consumption experience in itself is not meaningfully different from usual, surprise labeling might result in a perceived label–experience mismatch, ultimately leading to a curtailing of consumption. This research adopts a dual‐process perspective, providing evidence for both the cognitive appraisal of this label–experience mismatch and the heightened state of tense arousal accompanying this expectancy violation. Relatedly, we show that the negative consumption effect can be attenuated by increasing the degree of unexpectedness of the experience or by reducing tense arousal. Moreover, we show that consumers' dispositional need for cognitive closure moderates the observed consumption effect.